2017
DOI: 10.1186/s12889-017-4832-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prohibiting the use of Paraquat on pesticide-associated mortality

Abstract: BackgroundParaquat is associated with a high rate of fatalities in acute poisoning. This study aimed to examine the association between the national public health policy that banned the use of paraquat and the incidence of pesticide-associated mortality.MethodsAll external causes of death from 2009 to 2013 of Korea were analyzed. The intervention was a national public health policy that annulled the authorized use (2011) and banned the purchase of paraquat (2012). Two periods were compared as follows: before (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 28 publications
2
33
0
2
Order By: Relevance
“…Lung injury is characterized by acute chemical pulmonary interstitial lesions and the rapid development of pulmonary fibrosis, resulting in intractable hypoxemia and respiratory failure, which eventually leads to multiple organ damage or failure. [9,19] Currently, there is no specific method for clinical treatment of PQ poisoning. It is mainly treated through gastric lavage, catharsis, hemoperfusion, hemodialysis clearance of poisons, steroid impact therapy against organ damage and symptomatic support therapy, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Lung injury is characterized by acute chemical pulmonary interstitial lesions and the rapid development of pulmonary fibrosis, resulting in intractable hypoxemia and respiratory failure, which eventually leads to multiple organ damage or failure. [9,19] Currently, there is no specific method for clinical treatment of PQ poisoning. It is mainly treated through gastric lavage, catharsis, hemoperfusion, hemodialysis clearance of poisons, steroid impact therapy against organ damage and symptomatic support therapy, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Rotenone acts by inducing an increase in ROS production, elevating mitochondria bioenergetics, dysregulating intracellular calcium homeostasis, dysregulating autophagy, and altering lipid and glutamine metabolism [ 417 , 430 433 ]. Other examples of neurotoxins affecting mitochondrial function that are commonly used as Parkinson's models include 6-hydroxydopamine (6-OHDA) and paraquat, causing neurodegeneration via mitochondrial dysfunction and increase in free radicals [ 424 , 434 ]. In the following sections, we discuss how redox imbalance in the Parkinson's brain affects autophagy pathways to exacerbate the disease.…”
Section: Autophagy and Oxidative Stress In Parkinson'smentioning
confidence: 99%
“…In Korea, paraquat has been prohibited since 2011, and several studies have reported a decrease in suicide rates using this method since then. 25 26 However, strong regulation and control of pesticides should be maintained as the suicide rate through pesticide poisoning is still high among the elderly. 27 Similarly, in Korea, there is an effort to establish a poisoning information database to provide emergency treatment information for patients presenting to the ED with poisoning.…”
Section: Discussionmentioning
confidence: 99%